Neurotransfection activity of gene preparations: introduction to dressing formulations - Żaneta Słyk; Paulina Kruk; Sławomir Barszcz; Krzysztof Gawrychowski; Maciej Małecki (Polish Pharmaceutical Society, 2021)
Background Preparations for local anticancer therapy based on a biodegradable, dressing matrices are included in the treatment regimens of malignant gliomas of the brain. Radical resection of a neoplastic lesion is associated with the best clinical effect of treatment, however, the nature and location of the lesions often limit the scope of resection. The effectiveness of adjuvant methods such as systemic chemotherapy is limited primarily by the blood-brain barrier that is difficult to penetrate. New treatment techniques to target neoplastic cells remaining after surgical resection are searching. An interesting solution may be gene formulations for topical application, based on polymers used in dressing materials. Aim of the study The aim of this study was to evaluate the effectiveness of introducing gene preparations into mouse brain cells. Development of an ex vivo transduction / transfection model and comparison of the efficiency of viral vectors (rAAV) and non-viral vector (FuGENE®) were assumed. The aim of this study was to evaluate the effectiveness of introducing gene preparations into mouse brain cells. Development of an ex vivo transduction / transfection model and comparison of the efficiency of viral vectors (rAAV) and non-viral vector (FuGENE®) were assumed. Materials and methods The tissue of C57BL/6 laboratory mice strain were used. Brain cell mortality under the ex vivo transduction / transfection conditions was assessed. The efficiency of transfection method using the non-liposomal FuGENE® HD preparation and rAAV vector transduction method were analyzed using the standard methodology of a gene therapy laboratory. The evaluation of the itr sequences present in the rAAV / pDNA was performed by qPCR method. Results As a result of the research, a model of transduction / transfection of mouse brain cells using reporter viral vectors (rAAV) and the non-viral pAAV:FuGENE complex was developed. The optimal ex vivo transduction conditions were determined (temperature 37°C, time 60'). The possibility of transduction / transfection of brain cells with viral (rAAV) and non-viral (pAAV:FuGENE) gene preparations has been demonstrated. Based on the qPCR analysis, the efficiency of transduction / transfection for the rAAV9, rAAV9/DJ and pAAV:FuGENE vectors was estimated at 9.68E+06, 1.77E+06 and 3.73E+06 gc/50ng, respectively. The rAAV9 gene preparation was selected for further formulation studies. Conclusions Viral and non-viral vectors are useful tools for introducing transgenes into mouse brain cells in ex vivo conditions. Based on the recombinant rAAV9 gene vector, it is possible to conduct further research in the area of the development of gene dressings for neurooncological applications.